Enhancing Adolescent Mental Health: A Quasi-Experimental Study on the Impact of Combined Cognitive behavioral Therapy and Group Therapy - Estin Yuliastuti; Nurul Istiqomah; Yuli Widyastuti (Journal Of Nursing Practice, 2026)
Background: Adolescent mental health problems remain a major public health concern. Although Cognitive Behavioral Therapy (CBT) and group therapy have individually demonstrated effectiveness, evidence regarding their combined use among adolescents remains limited. Purpose: This study aimed to evaluate the effectiveness of combined CBT and group therapy in improving adolescent mental health. Methods: This quasi-experimental pre-test–post-test control group study with a 1:1 allocation ratio was conducted among 40 adolescents in Surakarta, Indonesia, from February to March 2024. Participants were recruited using a cluster-based sampling approach followed by total sampling of eligible students. The intervention group received CBT followed by group therapy over three consecutive sessions, whereas the control group received a delayed intervention after study completion. Mental health was assessed using the Strengths and Difficulties Questionnaire (SDQ). Data were analyzed using the Wilcoxon Signed-Rank Test and Mann–Whitney U Test, with effect sizes (r) calculated to determine the magnitude of the intervention effect Results: The intervention group demonstrated a significant improvement in SDQ scores following the intervention (Z = −3.18, p = 0.001; r = 0.71), whereas no significant change was observed in the control group (Z = −0.38, p = 0.705; r = 0.08). Post-intervention comparison showed significantly better mental health outcomes in the intervention group than in the control group (Z = −3.58, p < 0.001; r = 0.57), indicating a large intervention effect. Conclusion: The combination of CBT and group therapy significantly improved adolescents' mental health and demonstrated clinically meaningful benefits. This integrated intervention may be considered an effective early mental health strategy for adolescents and has potential for implementation in nursing practice, school mental health programs, and community mental health services when delivered by appropriately trained professionals.